Applications of Single-Molecule Vibrational Spectroscopic Techniques for the Structural Investigation of Amyloid Oligomers - Vu, Katrin Ha Phuong (2022)
Amyloid oligomeric species, formed during misfolding processes, are believed to play a major role in neurodegenerative and metabolic diseases. Deepening the knowledge about the structure of amyloid intermediates and their aggregation pathways is essential in understanding the underlying mechanisms of misfolding and cytotoxicity. However, structural investigations are challenging due to the low abundance and heterogeneity of those metastable intermediate species. Single-molecule techniques have the potential to overcome these difficulties. This review aims to report some of the recent advances and applications of vibrational spectroscopic techniques for the structural analysis of amyloid oligomers, with special focus on single-molecule studies.